La relación subsidiaria y complementaria entre los sistemas nacionales de protección de derechos humanos y el sistema interamericano - Lengua Parra, Adrián (2017)
The author presents us the increasing force of the partnership between International Law and its entities by one side and the National States by the other, without impairing with its Sovereignty; and also how this process has created a surveillance and supervision praxis, focused on the possibility that State activities may affect the rights of its citizens.This article includes as well a survey on the theory and legal precedents that are most noteworthy, pointing to comprehend the passing from a subsidiary vision of the international legal order towards the national to one that is complementary, without prejudice to unpolished or unfinished aspects of the agenda. Everything in order to the full effect of Human Rights.